Comentarios sobre algunos índices para medir el nivel y el cambio de la mortalidad - Arriaga, Eduardo E. (El Colegio de México A.C., 1996)
The level and change of mortality can be measured in several ways not only because the selected index, but also because of the way that the mortality change is measured.This document considers the indexes more frequently used for measuring the level of mortality, including the one of years of life lost recently developed. Each index is analyzed in relation to its accuracy for measuring the level and change of mortality, and advantages and disadvantages of each of them are discussed. The index years of life lost is presented with some details, since it was developed rather recently.